Matching and Agglomeration: Theory and Evidence From Japanese Firm‐to‐Firm Trade - Miyauchi, Yuhei (Econometrica, 2024)
This paper shows that matching frictions and a thick market externality in firm‐to‐firm trade shape the agglomeration of economic activity. Using panel data of firm‐to‐firm trade in Japan, I demonstrate that firms gradually match with alternative suppliers following an unanticipated supplier bankruptcy, and that the rate of rematching increases in the geographic density of alternative suppliers. Motivated by these empirical findings, I develop a general equilibrium model of firm‐to‐firm matching in input trade across space. The model reveals that the thick market externality gives rise to an agglomeration externality affecting regional production and welfare. Using the calibrated model to the reduced‐form patterns of firm‐to‐firm matching, I estimate that the elasticity of a region's real wage with respect to population density due to the thick market externality is approximately 0.02. This finding highlights the substantial impact of the thick market externality on the overall agglomeration benefit.